Frontispiece: The Donor‐Base‐Free Aggregation of Lithium Diisopropyl Amide in Hydrocarbons Revealed by a DOSY Method. Issue 24 (8th June 2015) - Neufeld, Roman; John, Michael; Stalke, Dietmar
<x xml:space="preserve">Abstract</x> Lithium Amides In their Communication on page 6994 ff., D. Stalke and co‐workers describe DOSY NMR experiments applied to study the state of aggregation of lithium diisopropyl amide in solution.